Contemporary views on personal identity formation - Karaś, Dominika; Topolewska-Siedzik, Ewa; Negru-Subtirica, Oana (Studia Psychologica: Theoria et praxis, 2018)
Identity development is undoubtedly one of the most crucial tasks in human life. Identity is also one of the most frequently examined issues in contemporary developmental psychology research. In the literature, we can find various definitions of identity, as well as various theoretical conceptualizations and models. The present paper describes contemporary models of personal identity, provides the definitions of the notions (as processes/dimensions/styles/modes) included in these models, measurement methods, as well as a review of the research results obtained in these various theoretical paradigms. The review includes multiple approaches – from Marcia’s classical identity status paradigm, through neo-Eriksonian models (such as the three and five dimensional models, identity styles, identity processes in adulthood) up to narrative views. Finally, we present conclusions based on the analyses of these models and implications for future research and theory.